Effect of glass fiber non-dental’s length and position on the flexural strength of FRC - Adella Syvia Maharani; Widjijono Widjijono; Endang Wahyuningtyas (Majalah Kedokteran Gigi Indonesia, 2019)
Glass fiber non-dental has a similar composition to E-glass fiber dental that commonly used as fiber reinforced composite (FRC) materials in resin bonded prosthesis. Fiber effectiveness can be determined by the length and the position. The aim of this study was to examine the effect of glass fiber non dental’s length and position on the flexural strength of FRC in resin bonded prosthesis. This study has been done used 36 FRC samples with beam shaped (15 mm x 2 mm x 2 mm). Fiber reinforced composite  samples were consisted of 9 groups (a combination between length: 4 mm, 6 mm, and 12 mm and position: compression, neutral, tension zone). The flexural strength was tested by universal testing machine and statistically analyzed using two-way ANOVA (p<0.05). The result showed that the lowest (compression, 4 mm) and the highest (tension, 12 mm) flexural strength were 104.30 ± 13.90 MPa and 166.18 ± 8.59 MPa. The two-way ANOVA test showed that variation of position, length, and interaction between placement-length had a significant effect on the flexural strength (p<0.05). The conclusion of this study was fiber position on compression zone with 4 mm length had the lowest flexural strength. In addition, fiber position on tension zone with 12 mm length had the highest flexural strength.